The development of moral theology : five strands - Curran, Charles E. (Moral traditions series., 2013)
Charles Curran in his newest book The Development of Moral Theology: Five Strands, brings a unique historical and critical analysis to the five strands that differentiate Catholic moral theology from other approaches to Christian ethics-sin and the manuals of moral theology, the teaching of Thomas Aquinas and later Thomists, natural law, the role of authoritative church teaching in moral areas, and Vatican II. Significant changes have occurred over the course of these historical developments. In addition, pluralism and diversity exist even today, as illustrated, for example, in the theory of.